(untitled) (Materiali di Estetica. Terza serie, 2023)
The aim of this paper is to provide an account of the problem of truth by focusing on the recurring concept of Welt in the major works of Edmund Husserl and Martin Heidegger. The logical relevance of the relationship between the truth and the world, as highlighted by Husserl, will allow us to bring how we make sense of the world into focus. A brief examination of the main topics concerning Heidegger’s most relevant philosophical bequest, the notion of Dasein, will subsequently clarify the above-mentioned relationship in light of the bond the subject shares with other beings which inhabit the world. Finally, we will surmise that this could set up the prolegomena of a theory of signification as well.